If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 1 + -4x = 13 Reorder the terms: 1 + x + -4x = 13 Combine like terms: x + -4x = -3x 1 + -3x = 13 Solving 1 + -3x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 13 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 13 + -1 -3x = 13 + -1 Combine like terms: 13 + -1 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 5/8q=-20 | | 8x-13y=12 | | Y-5=m(x-6)form | | -18=-x-11 | | 8y+y^2=180 | | 8y+y^2=189 | | 0.54(6)+.06x=.18(24+x) | | f(4)=9x+7 | | -8+6x+4x=-98 | | 13x+1=9x+5 | | 3(c-63)=27 | | 5x-9+3x=87 | | f(5)=3x+x^2 | | (X-2)/10=(x-7)/5 | | X+325=520 | | f(x)=3x+x^2 | | 4x+10-2x=-10 | | 3(k+9)=72 | | -t+-6=-10 | | 32(x-1)+115x+10(x+2)=1607 | | -24=8(r+63) | | 43=2x+2x+7 | | 3/7x3 | | 3h+2=-4 | | -2x-2+5x=16 | | 4(b-73)+44=60 | | 7-3m=13-5m | | p=15x-1000 | | 20=5+3m | | -4x+9+6x=23 | | (3x)/5=6/1 | | 10-2b^2=-88 |